Enhancing the growth performance of replacement female breeder goats through modification of feeding program - Abdul Ghani, Ahmad Afifi; Shahudin, Muhammad Syafiq; Saad, Mohd Zamri; Abu Bakar @ Zakaria, Md Zuki; Haron, Abd Wahid; Kasim, Azhar; Salisi, Mohd Shahrom; Abu Hassim, Hasliza (Veterinary World, 2017)
Aim: The study was conducted at a smallholder goat farm located in Labu, Negeri Sembilan, Malaysia. The objective of this study was to evaluate the effect of proper feeding program on growth performances of replacement breeder goats. Materials and Methods: A total of 30 healthy female boer cross goats at the age of 4 months old with average initial live body weight (BW) of 20.05±0.5 kg were used for on-farm feeding trial to evaluate the growth performance as preparation for breeding purposes. The experimental goats were divided into two groups of 15 animals each labeled as control and treatment groups, which were kept under intensive farming system. Goats in control group were fed with normal routine feeding protocol practiced by the farmer, while goats in the treatment group were fed with new feed formulation. Throughout the experimental period, on-farm monitoring and data collection were carried out. Initial BW and body condition score (BCS) were recorded before the start of the experiment while final BW and BCS were gained after 7 months of the experimental period. Average daily gain (ADG) was calculated after the experiment end. Data on BW, ADG, and BCS were recorded from both groups for every 2 weeks and reported monthly. The feed intake for the control group was 2.8 kg/animal/day which practiced by the farmer and 3.2 kg/animal/day as new feed formulation for the treatment group. Results: After 7 months of the experimental period, final BW shows an improvement in treatment group (39.1±1.53 kg) compared with control group (32.3±1.23 kg). The ADG in treatment group also gives promising result when comparing with control group. Goats in treatment group significantly attained better ADG than control group which were 126.7 g/day and 83.3 g/day, respectively. For the BCS, goats in the treatment group had shown an improvement where 86.67% (13 out of 15) of the group had BCS≥3 (1-5 scoring scale) and only 66.67% (10 out of 15) of the control group had BCS≥3. Conclusion: Therefore, it was concluded that implementation of proper feeding program as shown in treatment group give promising result to improve the growth performance of replacement breeder goats which can be adopted by the farmers to improve farm productivity.